Education under Attack in Cameroon: The Effects of the Socio-Political Crisis on the Anglophone Sub-System of Education of the Anglophone Regions of Cameroon - Tande Kate Eposi; Molua Patrick Ewange (International Journal on Integrated Education, 2021)
Cameroon’s Anglophone regions have been the theatre of an armed conflict since late 2017 between government forces and Anglophone Non-state armed groups (NSAG). The sociopolitical crisis that started in 2016 has deteriorated overtime and has led to violent clashes between armed forces, killings, internal displacement and a growing atmosphere of fear, insecurity and incertitude. In late 2016, Anglophone Common Law lawyers and Teachers’ Trade Unions organized peaceful strikes across the two Anglophone regions to denounce among others, the systematic assimilation process of the Anglo-Saxon legal and education system into the Francophone system. According to them, the educational system is made up of two sub systems: the Anglophone subsystem of education based on the Anglo-Saxon model and the Francophone subsystem following the French model, and each must maintain its peculiarities. In response to the strikes, the government clamped down on the Common Law lawyers and Anglophone peaceful protesters who joined the protests to denounce the perceived marginalization and assimilation of Anglophones. By late 2017, the situation quickly degenerated into an armed conflict with Anglophone Non-state armed groups transforming the teachers’ strike into a school boycott campaign, shutting down education in most parts of the Anglophone regions. As a result, the education sector came under attack by the burning of schools and attacks on students, teachers, parents and education officials by Non-state armed groups. This situation has had devastating effects on the education sector as several hundreds of thousands of school children and students have been deprived of education since 2016. The purpose of this paper is to examine the reasons why education is under attack in the Anglophone regions of Cameroon.